Scrawl : a novel - Shulman, Mark, 1962-; local (New York : Roaring Brook Press, 2010)
When eighth-grade bully Tod and his friends get caught committing a crime on school property, his penalty, staying after school and writing in a
"A Neal Porter Book."
Sequoyah Nominee 2013
journal, reveals aspects of himself that he prefers to keep hidden.
Keywords: Lexile; sears -- Self-perception; sears -- Poverty; sears -- Bullies; sears; sears; sears -- Diaries